Levothyroxine Interactions with Food and Dietary Supplements-A Systematic Review - Agnieszka Wiesner; Danuta Gajewska; Paweł Paśko (MDPI AG, 2021)
Levothyroxine (l-thyroxine, l-T4) is a drug of choice for treating congenital and primary hypothyroidism. Although clinically significant interactions between l-T4 and food can alter the safety and efficacy of the treatment, they still seem to be generally underestimated by patients, physicians and pharmacists. This review aimed to investigate the effects of meals, beverages, and dietary supplements consumption on l-T4 pharmacokinetics and pharmacodynamics, to identify the most evident interactions, and to perform the recommendations for safe co-administering of l-T4 and food. A total of 121 studies were identified following a systematic literature search adhering to PRISMA guidelines. After full-text evaluation, 63 studies were included. The results proved that l-T4 ingestion in the morning and at bedtime are equally effective, and also that the co-administration of l-T4 with food depends on the drug formulation. We found limited evidence for l-T4 interactions with coffee, soy products, fiber, calcium or iron supplements, and enteral nutrition but interestingly they all resulted in decreased l-T4 absorption. The altered l-T4 efficacy when ingested with milk, juices, papaya, aluminium-containing preparations, and chromium supplements, as well as observed enhancement effect of vitamin C on l-T4 absorption, shall be further investigated in larger, well-designed studies. Novel formulations are likely to solve the problem of coffee, calcium and iron induced malabsorption of l-T4. Maintaining a proper time interval between l-T4 and food intake, especially for coffee and calcium, or iron supplements, provides another effective method of eliminating such interactions.